(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Uzbek and English are only two of the languages that have been greatly impacted by the growing globalisation of sports. Broader linguistic, cultural, and social shifts are reflected in the development, modification, and integration of sports terminology in both languages. This research investigates how sports terminology functions in contemporary Uzbek and English, looking at its history, evolution, and effects on everyday interactions, media, and communication. Over decades, historical occurrences, technical developments, and international tournaments have all affected the evolution of sports terminology in the English language system. Because English-speaking nations dominate sports administration and media, several English sports words, including "goal," "offside," "penalty," and "tournament," have been extensively adopted across languages. Sports’ international appeal has helped English words, sometimes with little alteration, proliferate into other languages. On the other hand, due to linguistic and historical influences, the Uzbek language has undergone a distinctive process of assimilating sports terms. Numerous phrases of Russian origin were incorporated into Uzbek sports jargon during the Soviet era. Nonetheless, there has been an increasing tendency to use local or foreign English terminology since Uzbekistan gained its independence. Some terminology have been localised to conform to Uzbek phonetics and syntax, while others, like "futbol" (football), "tennis," and "basketbol" (basketball), have been directly pulled from English. The mechanics of word development in sports terminology, including borrowing, calquing, and semantic changes, are also examined in this study. It draws attention to how ubiquitous sports-related terminology has become thanks to the media, education, and internet platforms. Additionally, the study looks at how language policy, lexical standardisation, and public perception in both linguistic groups are impacted by the dynamic growth of sports terminology. In the end, this study emphasises how important sports terminology is to contemporary language interaction, promoting intercultural dialogue and enhancing both Uzbek and English. The results advance our knowledge of linguistic globalisation and the relationship between language, culture, and sports in general.